Role of Q-type Ca2+ channels in vasopressin secretion from neurohypophysial terminals of the rat. - Wang, G (1997)
1. The nerve endings of rat neurohypophyses were acutely dissociated and a combination of pharmacological, biophysical and biochemical techniques was used to determine which classes of Ca2+ channels on these central nervous system (CNS) terminals contribute functionally to arginine vasopressin (AVP) and oxytocin (OT) secretion. 2. Purified neurohypophysial plasma membranes not only had a single high-affinity binding site for the N-channel-specific omega-conopeptide MVIIA, but also a distinct high-affinity site for another omega-conopeptide (MVIIC), which affects both N- and P/Q-channels. 3. Neurohypophysial terminals exhibited, besides L- and N-type currents, another component of the Ca2+ current that was only blocked by low concentrations of MVIIC or by high concentrations of omega-AgaIVA, a P/Q-channel-selective spider toxin. 4. This Ca2+ current component had pharmacological and biophysical properties similar to those described for the fast-inactivating form of the P/Q-channel class, suggesting that in the neurohypophysial terminals this current is mediated by a 'Q'-type channel. 5. Pharmacological additivity studies showed that this Q-component contributed to rises in intraterminal Ca2+ concentration ([Ca2+]i) in only half of the terminals tested. 6. Furthermore, the non-L- and non-N-component of Ca(2+)-dependent AVP release, but not OT release, was effectively abolished by the same blockers of Q-type current. 7. Thus Q-channels are present on a subset of the neurohypophysial terminals where, in combination with N- and L-channels, they control AVP but not OT peptide neurosecretion.